Rungia gialaiensis (Acanthaceae), a new species from the Central Highlands of Vietnam - Hai, Do Van; Hoan, Duong Thi; Lin, Zheli; Deng, Yunfei; Choudhary, Ritesh Kumar; Lee, Joongku (Phytotaxa, 2021)
Rungia gialaiensis, a new species endemic to Gia Lai Province in the Central Highlands of Vietnam, is described and illustrated. It is morphologically allied to R. daklakensis and R. khasiana, but differs from both in its stoloniferous branches growing from leaf axils.